(untitled) (INNOVATIVE ECONOMY, 2025)
Pylypenko H.M. INVESTMENT ATTRACTIVENESS OF THE ECONOMY IN THE CONTEXT OF ECONOMIC POWER INSTITUTIONS TRANSFORMATION Purpose. The aim of the article is to improve the categorical apparatus of the investment sphere by distinguishing concepts that reflect the process of making investment decisions and clarifying the role of economic power in ensuring the investment attractiveness of the country. Methodology of research. The study is based on the use of the method of scientific abstraction, combining of which with a systemic approach allowed us to distinguish the concepts of «investment attractiveness», «investment potential», «investment climate» and «economic power». By applying the structural-functional method, the elements of economic power were identified and their connection with the concept of “state power” was demonstrated. The empirical basis of the study was UNCTAD reports on world investment. Findigs. The analysis of theoretical and methodological approaches used in domestic economic science in the study of factors affecting the formation of investment attractiveness of the national economy was carried out. It was found out that in economic discourse, such concepts as “investment attractiveness”, “investment potential”, “investment climate”, “economic power” coexist and are often used as synonyms. On the basis of the application of the subject-object approach to the study of economic phenomena and processes, a distinction was made between similar, although different in content, concepts that form the categorical apparatus of investment theory. The key factor of influence on the conditions of investment activity in a certain territory, and, accordingly, on the possibility of attracting foreign investments, is found to be the economic power. The latter is considered as the power of the state, which is manifested in the ability of the government to create laws and ensure their implementation, to conduct an effective tax policy, to establish the limits of freedom and necessity between economic entities, as well as to form the economic consciousness of the nation through ideological levers. The connection of these forms of manifestation of economic power with political power creates a basis for considering the strength of the state and its ability to implement control over economic resources within the national economy. On the basis of the analysis of global trends in international capital movement, the correlation between economic power and the state’s ability to form investment potential and create a favourable investment climate for attracting foreign direct investment to its territory is demonstrated. Originality. It was established that the categories “investment potential” and “investment climate” reflect the objective side of investment activity, while the concept of “investment attractiveness” is a subjective reflection of the conditions and factors of the national economy that affect the expected profitability of investments. It is proven that the objective conditions of investment activity are formed under the influence of economic power, the basis of which is the power of the state. Practical value. Clarification of concepts that reflect the processes of investment decision-making is of important methodological and practical importance. On the one hand, this allows to establish cause-and-effect correlations between phenomena, and on the other hand, to form an effective system of economic policy levers aimed at forming the investment attractiveness of the national economy. Key words: investment attractiveness, investment climate, international capital flows, foreign investments, GDP, sustainable development, institutions of economic power, new configuration of economic power.